Microencapsulação de kefir pela técnica de gelificação iônica para aplicação em alimentos - Correia, Hugo José de Araújo (2022)
Kefir is a complex food, as its microbiological composition aggregates a large number of symbiotic microrganisms, of which several bacteria have been identified as probiotic. However, its strong aroma and sour taste are unappreciated by most people. So, a good alternative to improve the consumption of this food is microencapsulation. A technique in which microdrops of an active ingredient are surrounded by a homogeneous or heterogeneous coating, congruent to capsules with many applications, so that it is protected against external factors, masking unpleasant aromas, and allowing the development of products with high added value. One of the viable microencapsulation techniques is the ionic gelation method, that is, a reaction between a polymeric solution and an ionic solution. Given the above, the objective of this study was to develop microcapsules of kefir, to be consumed individually or with other foods; and analyze the stability of probiotics, as well as the physical, physicochemical and microbiological changes in the product (kefir) and in the microcapsules made from it, during refrigerated storage at 5±1 °C for 28 days in transparent glass packaging. Analyzes were performed in triplicate and Tukey's test (p < 0.05) was applied for comparisons of means, with the results expressed as mean ± standard deviation. During storage, there was a product with microorganism counts within the standards for lactic acid bacteria around 107CFU/mL and yeast 104 CFU/mL at the end of 28 days of storage. It was observed that there was no significant difference (p > 0.05) in the number of lactic acid bacteria between kefir and microcapsules during the storage period; but there was in the number of lactic acid bacteria in kefir in the 28 days. So, microencapsulation of kefir was effective in protecting lactic acid bacteria from adverse environmental conditions. The pH of kefir and the pH of the microcapsules showed a significant difference between them in the initial and final time. The initial titratable acidity of kefir and microcapsules was 1.05% and 0.66%, respectively. As kefir has a high acidity, its fresh consumption is not well accepted. So, the reduction of acidity in the microcapsules added value to them, as they can be consumed as a more palatable product. Thus, obtaining kefir microcapsules had positive points due to the formation of a product with a high nutritional and functional value, which can be applied in the formulation of innovative foods, helping to prevent many diseases and thus potentially benefiting the health of the consumers.